PENGEMBANGAN MEDIA AUDIO VISUAL UNTUK PERILAKU HIDUP SEHAT DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SISWA KELAS 2 SD NEGERI PORIS PELAWAD 3 - Ahmad Edo Erdian; Romi Ramdon Ginanjar; Mardion (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to produce an audio visual media product and learn healthy living behavior, especially hand and foot hygiene, for class II students at SD Negeri Poris Pelawad 3, Cipondoh District, Tangerang City. This research is research and development regarding the development of audio visual media in learning healthy living behavior, especially hand and foot hygiene. The population in this study were class II students at SDN Poris Pelawad 3 with a total of 19 children. The research instrument is in the form of evaluation sheets for material experts, media experts and language experts in the form of product validity results. The instrument in the form of product validity is obtained by using a questionnaire and an evaluation sheet that has been made based on the assessment. The data analysis technique used is a qualitative and quantitative approach. Research data were analyzed using descriptive analysis techniques. This research produces a product in the form of audio-visual media packaged in the form of a compact disk (CD). The validation results from material experts received the "very good" category, the validation results from media experts received the "very good" category and the validation results from language experts received the "very good" category. The test results for individual respondents, small groups and large groups were "very good". Based on the results of this assessment, it can be concluded that audio-visual learning media for material on physical education, sports and health, in particular material on hand and foot health behavior for class II students at SD Negeri Poris Pelawad 3, Cipondoh District, Tangerang City, is suitable for use as a source of material. teach.